Coronary artery calcium score on standard of care oncologic CT scans for the prediction of adverse cardiovascular events in patients with non-small cell lung cancer treated with concurrent chemoradiotherapy - Koutroumpakis, Efstratios; Xu, Ting; Lopez-Mattei, Juan; Pan, Tinsu; Lu, Yang; Irizarry-Caro, Jorge A.; Mohan, Radhe; Zhang, Xiaodong; Meng, Qing H.; Lin, Ruitao; Xu, Tianlin; Deswal, Anita; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Chemoradiotherapy (CRT) has been associated with increased incidence of cardiovascular (CV) adverse events (CVAE). Coronary artery calcium scoring (CAC) has shown to predict coronary events beyond the traditional CV risk factors. This study examines whether CAC, measured on standard of care, non-contrast chest CT (NCCT) imaging, predicts the development of CVAE in patients with non-small cell lung cancer (NSCLC) treated with CRT. Methods: Patients with NSCLC treated with CRT at MD Anderson Cancer Center from 7/2009 until 4/2014 and who had at least one NCCT scan within 6 months from their first CRT were identified. CAC scoring was performed on NCCT scans by an expert cardiologist and a cardiac radiologist following the 2016 SCCT/STR guidelines. CVAE were graded based on the most recent Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. CVAE were also grouped into i. coronary/vascular events ii. arrhythmias or iii. heart failure. All CVAE were adjudicated by a board-certified cardiologist. Results: Out of 193 patients, 45% were female and 91% Caucasian. Mean age was 64 ± 9 years and mean BMI 28 ± 6 kg/m2. Of 193 patients, 74% had CAC > 0 Agatston units (AU), 49% CAC>100 AU and 36% CAC >300 AU. Twenty-nine patients (15%) developed a grade >2 CVAE during a median follow up of 24.3 months (IQR: 10.9-51.7). Of those, 11 (38%) were coronary/vascular events. In the multivariate cox regression analysis, controlling for mean heart dose and pre-existing CV disease, higher CAC score was independently associated with development of a grade >2 CVAE (HR: 1.04, 95% CI: 1.01-1.08, p=0.022 [per 100 AU increase]) and with worse overall survival (OS; CAC>100 vs <100 AU, HR: 1.64, 95% CI: 1.11-2.44, p=0.013). In a sub-analysis evaluating the type of the CVAE, it was the coronary/vascular events that were significantly associated with higher baseline CAC (median: 676 AU vs 73 AU, p=0.035). Conclusions: CVAEs are frequent in patients with NSCLC treated with CRT. CAC calculated on “standard of care” NCCT can predict the development of CVAEs and specifically coronary/vascular events, as well as OS, independently from other traditional risk factors and radiation mean heart dose.